Los precedentes medievales del criticismo kantiano - Fernández Polanco, Valentín (Revista de Filosofía, 2003)
This article aims to show the bond that, following André de Muralt, can be stablished between kantian criticism and critical late-scholastic thought of 14th century. In order to that, it shows firstly a structural community between both kantian and scottish formalism, which is due to the sistematic use of formal distinction ex natura rei in the construction of kantian criticism, and, secondly, a thematic conti- nuity between the copernic turn operated by Kant and the reform of causality operated by the ockhamian hypothesis de potentia absoluta dei. It concludes to underline the affinities – more than the contrasts – in the Duns Scot’s and William of Ockham’s theological bases, as well as the theological dependence of philosophy builted on that bases.